2016
DOI: 10.1534/genetics.116.188532
|View full text |Cite
|
Sign up to set email alerts
|

Linking Gene Expression in the Intestine to Production of Gametes Through the Phosphate Transporter PITR-1 inCaenorhabditis elegans

Abstract: Inorganic phosphate is an essential mineral for both prokaryotic and eukaryotic cell metabolism and structure. Its uptake into the cell is mediated by membrane-bound transporters and coupled to Na+ transport. Mammalian sodium-dependent Pi cotransporters have been grouped into three families NaPi-I, NaPi-II, and NaPi-III. Despite being discovered more than two decades ago, very little is known about requirements for NaPi-III transporters in vivo, in the context of intact animal models. Here we find that impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Signaling between the intestine and other tissues has also been documented. For example, the gonad is able to communicate to the intestine to regulate vitellogenin production ( Balklava et al 2016 ) whereas the intestine can regulate germline sex determination via specific signaling fatty acids ( Tang and Han 2017 ). Similarly, the hypodermis can modulate lipid accumulation in the intestine via a sma-3 dependent signal ( Clark et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling between the intestine and other tissues has also been documented. For example, the gonad is able to communicate to the intestine to regulate vitellogenin production ( Balklava et al 2016 ) whereas the intestine can regulate germline sex determination via specific signaling fatty acids ( Tang and Han 2017 ). Similarly, the hypodermis can modulate lipid accumulation in the intestine via a sma-3 dependent signal ( Clark et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional interesting finding in this study was the detection of several germline defects (vitellogenin uptake defect, increased apoptosis, defects in membranes of maturing oocytes), which all likely contribute to the low brood size of the paqr-2 and iglr-2 mutants. The accumulation of VIT-2::GFP in the pseudocoelom of the paqr-2 and iglr-2 mutants likely reflects a defect of the gonad to take up vitellogenins; this defect leads to increased production of vitellogenins by the intestine because of feedback mechanism between the germline and intestine ( Balklava et al 2016 ). This does not necessarily imply a primary gonad sheath membrane defect: others have shown that omega-6 PUFAs are essential for germline development ( Chen et al 2016 ) and to regulate the balance of lipid stores between the soma and germ cells ( Lynn et al 2015 ), and their production, or that of other regulatory lipids, may be defective in the paqr-2 and iglr-2 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In a forward genetic screen for receptor-mediated endocytosis mutants that accumulate yolk at high levels in the pseudocoelom, Balklava et al (2016) identified pitr-1 , encoding an inorganic phosphate membrane transporter. Surprisingly, rather than disrupting yolk endocytosis, this mutant caused yolk build-up by increased vitellogenin expression at both the mRNA and protein levels.…”
Section: Regulation Of Vitellogenins In C Elegansmentioning
confidence: 99%
“…Anatomically, the intestine and the germ cells are very closely located in C. elegans . The close link between nutrient export from the intestine and the production of gametes by the germ line was previously proposed [39]. Additionally, the existence of a crosstalk between the intestine and the germ line has been shown through the removal of germline stem cells, which resulted in increased fat accumulation in the intestine derived from unconsumed yolk [40,41].…”
Section: Resultsmentioning
confidence: 99%